Housing management practices followed by buffalo farmers of peri-urban areas of Surat city of Gujarat - Sabapara, G P; Patel, N B (Indian Journal of Animal Production and Management, 2018)
A study was conducted purposively in peri-urban areas of Surat city of Gujarat to ascertain the housingmanagement practices for buffalo and data was collected from randomly selected 50 buffalo farm ownersthrough personal interview with the help of pre-tested structured schedule. The study revealed that majorityof respondents provided open and kutcha type houses (70%), kept their buffaloes inside the house bothduring day and night (94%), constructed buffalo sheds nearby their dwelling (68%), the buffalo sheds wereoriented in east-west direction (84%), had double row system of animal housing (82%) and had optimumsized animal house (94%). Total 96, 98, 74, 90, 86, 66, 78, 60, 90, 86, 86 and 30% of respondents hadadequate floor space, provision of sufficient light, good ventilation, cleanliness, pucca floors, slope in floorstowards back, cemented type poles, double slope type of roof, provision of any type of manger, pucca typeof manger, pucca drainage facility of urine and provided bedding materials in their buffalo sheds respectively.